2022
DOI: 10.1186/s12889-021-12274-7
|View full text |Cite
|
Sign up to set email alerts
|

Household solid waste management practices and perceptions among residents in the East Coast of Malaysia

Abstract: Background Poor waste disposal practices hamper the progress towards an integrated solid waste management in households. Knowledge of current practices and perception of household solid waste management is necessary for accurate decision making in the move towards a more sustainable approach. This study investigates the household waste practices and perceptions about waste management in Panji, one of the sub-districts in Kota Bharu, Kelantan, Malaysia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 224 publications
(83 citation statements)
references
References 69 publications
5
72
1
5
Order By: Relevance
“… 14 The present finding is supported by studies conducted in Ethiopia. 10 , 12 However, a study conducted on Malaysia by Fadhullah et al 5 revealed that 74.3% of households disposed of food debris as waste. In this study, only (25.4%) of households segregated their solid waste at the source.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 14 The present finding is supported by studies conducted in Ethiopia. 10 , 12 However, a study conducted on Malaysia by Fadhullah et al 5 revealed that 74.3% of households disposed of food debris as waste. In this study, only (25.4%) of households segregated their solid waste at the source.…”
Section: Discussionmentioning
confidence: 99%
“… 30 In addition, about 95.9% of the respondents were aware that improper waste management leads to disease; such as diarrhea and malaria in Malaysia. 5 A possible explanation for this could be the lack of awareness on the danger posed by improper solid waste disposal in the Fiche town.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations